Quantification of synthetic cannabinoids in herbal smoking blends using NMR. Issue 5 (12th July 2016) - Dunne, Simon J.; Rosengren‐Holmberg, Jenny P.
Abstract : Herbal smoking blends containing synthetic cannabinoids have become popular alternatives to marijuana. These products were previously sold in pre‐packaged foil bags, but nowadays seizures usually contain synthetic cannabinoid powders together with unprepared plant materials. A question often raised by the Swedish police is how much smoking blend can be prepared from certain amounts of banned substance, in order to establish the severity of the crime. To address this question, information about the synthetic cannabinoid content in both the powder and the prepared herbal blends is necessary. In this work, an extraction procedure compatible with direct NMR quantification of synthetic cannabinoids in herbal smoking blends was developed. Extraction media, time and efficiency were tested for different carrier materials containing representative synthetic cannabinoids. The developed protocol utilizes a 30 min extraction step in d4 ‐methanol in presence of internal standard allowing direct quantitation of the extract using NMR. The accuracy of the developed method was tested using in‐house prepared herbal smoking blends. The results showed deviations less than 0.2% from the actual content, proving that the method is sufficiently accurate for these quantifications. Using this method, ten synthetic cannabinoids present in sixty‐three different herbal blends seized by the Swedish police between October 2012 and April 2015 were quantified. Obtained results showed a variation in cannabinoid contents from 1.5% ( w/w ) for mixtures containing MDMB‐CHMICA to over 5% ( w/w ) for mixtures containing 5F‐AKB‐48. This is important information for forensic experts when making theoretical calculations of production quantities in legal cases regarding "home‐made" herbal smoking blends. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A simple extraction procedure for direct NMR quantification of synthetic cannabinoids in Spice materials was developed and used in order to gain knowledge of common concentrations of synthetic cannabinoids in seized herbal smoking blends.